CYFRA21-1 tests in the diagnosis of non-small cell lung cancer: A meta-analysis. Issue 3 (September 2019) - Fu, Lei; Wang, Rong; Yin, Ling; Shang, Xiaopu; Zhang, Runtong; Zhang, Pengjun
Objective: The aim of the study was to evaluate the diagnostic value of soluble fragment of cytokeratin 19 (CYFRA21-1) tests in detecting non-small cell lung cancer (NSCLC), including squamous cell carcinoma, lung adenocarcinoma, and large cell carcinoma. Methods: The relevant studies were identified from PubMed, Embase and the Cochrane Library before November 2018. Summary estimates for sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio of CYFRA21-1 tests for the diagnosis of NSCLC were calculated using the random effects model. A summary receiver operating characteristic (SROC) curve was used to assess the overall effectiveness of the test. Meta-DiSc 1.4 and Stata11.0 were applied to the statistical analysis. Publication bias was detected using Egger's test. Results: A total of 22 studies consisting of 7910 NSCLC patients (squamous cell carcinoma/lung adenocarcinoma/large cell carcinoma) and 2630 benign lesions patients that met the inclusion criteria were included. The meta-analysis showed that CYFRA21-1 tests had a relatively high accuracy for squamous cell carcinoma detection and a lower accuracy for lung adenocarcinoma detection. The overall sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio of CYFRA21-1 tests for squamous cell carcinoma detection were 0.72 (95% confidence interval (CI) 0.70, 0.74), 0.94 (95% CI 0.92, 0.95), 9.73 (95% CI 7.06, 13.40), 0.37 (95% CI 0.29, 0.47), and 27.30 (95% CI 17.68, 42.16), respectively. The area under the SROC curve was 0.9171 (Q* = 0.8500). No publication bias was tested in the squamous cell carcinoma (P = 0.567) and lung adenocarcinoma (P = 0.378) groups. Conclusions: CYFRA21-1 tests might be appropriate for detecting squamous cell carcinoma.